Terapi Kompres Hangat Dalam Penerapan Respectful Women Care Terhadap Nyeri Haid (Dismenore) Pada Remaja Putri Di Asrama MAN 2 Yogyakarta - Mita Meilani; Amilya Pradita; Risky Puji Wulandari; Alief Nur Insyiroh Abidah (NHM PRESS, 2023)
Dysmenorrhea is menstrual pain that is felt before or during menstruation which is usually crampy in nature and is centered on the lower abdomen and sometimes is so severe that it interferes with activities. Dysmenorrhea also has a psychological impact in the form of emotional conflict, tension, and anxiety. This can create an uncomfortable and foreign feeling. Dysmenorrhea can be treated with pharmacological and non-pharmacological therapy. Non-pharmacological therapy includes warm compresses, exercise and relaxation. Consultation with a doctor about dysmenorrhea can also help in dealing with dysmenorrhea. The purpose of this study was to determine the effect of warm compresses on menstrual pain. This research method is a type of quantitative research with a quasi-experimental design. The research design is nonequivalent pre-test and post-test control group design. The number of samples used was 30 respondents who were divided into 2 groups, namely 15 students in the intervention group and 15 students in the control group. Conclusion: the decrease in the intensity of menstrual pain in young women who were given warm compresses was greater than those who were not given warm compresses. The average difference in the reduction of perineal wound pain in the control group was 1.54 and the intervention group had an average decrease in pain of 2.94.